Retraction to “A Qualitative Study of Sexual Behavior among Indonesian Married Men with Migrant Worker Wife” - Rifai, Ahmad; Afandi, Alﬁd Tri; Saputra , Kresna Ade (KnE Life Sciences, 2019)
Ahmad Rifai, Alfid Tri Afandi, and Kresna Ade Saputra Published online: October 10, 2019 Retracted: August 10, 2023 This article has been retracted as it was inadvertently published multiple times in this issue. Please note that the findings of the article remain valid. To view the article version of the record, please visit A Qualitative Study of Sexual Behavior among Indonesian Married Men with Migrant Worker Wife | KnE Life Sciences (knepublishing.com); https://doi.org/10.18502/kls.v4i13.5247 Corresponding Author: Ahmad Rifai Email: ahmadrifai@unej.ac.id